Implementasi Pemanfaatan Web Service Pada Layanan Puskesmas Kabupaten Musi Banyuasin - Hesa Bimantara; Hutrianto Hutrianto (Journal of Software Engineering Ampera, 2021)
Information technology is currently developing very rapidly and affects various aspects of life and the profession, one of which is in the field of health services, in various places, be it health centers, clinics or hospitals. The party will definitely record in detail the medical results of someone who is receiving treatment, that is what is called a medical record. Some of the puskesmas in the Musi Banyuasin district, especially the Tanah Abang puskesmas, are located in the district. Batanghari leko still doesn't have a decentralized database which means it doesn't have centralized storage. Web service itself is a liaison that allows various systems to communicate without being affected by platform differences. Web services also provide existing services on the old system to be able to communicate with the new system without making changes to both. This study was simulated at Tanah Abang Public Health Center and Bukit Selabu Public Health Center in the Musi Banyuasin Regency with the aim of making it easier for doctors and health centers to obtain patient medical records in the shortest time.